Lagrangian Detection of Moisture Sources for the Southern Patagonia Icefield (1979–2017) - Langhamer, Lukas; Sauter, Tobias; Mayr, Georg J. (Frontiers in Earth Science, 2018)
The origin of moisture for the Southern Patagonia Icefield and the transport of moisture towards it are not yet fully understood. These quantities have a large impact on the stable isotope composition of the icefield, adjacent lakes and nearby vegetation, and is hard to quantify from observations. Clearly identified moisture sources help to interpret anomalies in the stable isotope compositions and contribute to paleoclimatological records from the icefield and the close surrounding. This study detects the moisture sources of the icefield with a Lagrangian moisture source method. The kinematic 18-day backward trajectory calculations use reanalysis data from the European Centre for Medium-Range Weather Forecasts (ERA-Interim) from January 1979 to January 2017. The dominant moisture sources are found in the South Pacific Ocean from 80◦ W to 160◦ W and 30◦S to 60◦ S. A persistent anticyclone in the subtropics and advection of moist air by the prevailing westerlies are the principal flow patterns. Most of the moisture travels less than 10 days to reach the icefield. The majority of the trajectories originate from above the planetary boundary layer but enter the Pacific boundary layer to reach the maximum moisture uptake 2 days before arrival. During the last day trajectories rise as they encounter topography. The location of the moisture sources are influenced by seasons, Antarctic Oscillation, El-Niño Southern Oscillation, and the amount of monthly precipitation, which can be explained by variations in the location and strength of the westerly wind belt.”